Marine fish parasitology : - Grabda, Jadwiga (Polish Scientific Publishers - Warszawa, 1991)
This volume aims to be a comprehensive work on marine fish parasitology intende for marine scientists and research workers, the sea-going staff concerned with fish processing and students of fisheries and ichthyology. The material covered ranges from identification of the fish parasites, their biology and life cycles to common invasion pathways and relationships within food chains. Emphasis is also placed on the economic effect of these parasites on the fish industry as well onthe prevention of human infections.